Answer:
[tex](6,-8)[/tex].
Step-by-step explanation:
We have been given a system of equations. We are asked to solve the given system.
[tex]y=\frac{1}{3}x-10...(1)[/tex]
[tex]2x+y=4...(2)[/tex]
From equation (2), we will get:
[tex]y=4-2x...(2)[/tex]
Upon substituting this value in equation (1), we will get:
[tex]4-2x=\frac{1}{3}x-10[/tex]
Upon multiply by 3 on both side, we will get:
[tex]3\cdot 4-3\cdot 2x=3\cdot \frac{1}{3}x-3\cdot 10[/tex]
[tex]12-6x=x-30[/tex]
[tex]12-6x-x=x-x-30[/tex]
[tex]12-7x=-30[/tex]
[tex]12-12-7x=-30-12[/tex]
[tex]-7x=-42[/tex]
[tex]\frac{-7x}{-7}=\frac{-42}{-7}[/tex]
[tex]x=6[/tex]
Upon substituting this in equation (2), we will get:
[tex]y=4-2(6)[/tex]
[tex]y=4-12[/tex]
[tex]y=-8[/tex]
Therefore, the solution for our given system of equations is [tex](6,-8)[/tex].